Revisando a “Bússola do Escrever”: práticas docentes e produtivismo acadêmico no Brasil (2006-2015) - Rocha Júnior, Ismael (2018)
This Thesis approaches the Academic Productivism considering teachers enrolled in the Education Graduate Programs. To portray and understand the dynamics in which they are involved from the existing dichotomy caused by the pressure to produce and vocation to teach, the challenge of questioning and producing on the theme and surviving in a contemporary society in the second decade of the 21st Century is the context where this thesis was built. Quantitative and qualitative approaches compose its methodological path. Starting from an extensive survey, considering dissertations and theses produced between 2006 and 2015 in all the Brazilian Post-Graduate Programs in Education, and in the articles published in the Portal Educ @, it was possible to identify how many and which approaches were made on the theme. This census on the academic universe of Education showed that Academic Productivism, quantitatively, is not relevant when compared to other topics most frequently addressed. For the quantitative survey, statistical tools were used, among them Lotka's Law, still little present in the Brazilian academic works. However, considering this approach, it was necessary to qualitatively analyze all collected material, revealing consistent and useful productions that leads to a better understanding of the Academic Productivism. The inconsistency between the two approaches rises the Conclusion that they are complementary rather than incoherent. And again this path points to the teacher, present and represented in the quantitative and qualitative approaches, showing another nefarious side of Academic Productivism: the researcher teacher as victim and agent in this scene. On him lies all pressures, demands, challenges and the need for survival. These two sides will point to the complementarity of the two approaches of this Thesis, a contribution to the study of the theme to understand another face of the Academic Productivism in Brazil